Amiodarone-related keratopathy and optic neuropathy: case report and literature review - Meng, Nana; Xia, Leizhou; Gong, Yiqing; Lu, Peirong (Frontiers in Medicine, 2025)
Amiodarone, a highly effective yet lipophilic antiarrhythmic drug with prolonged half-life, is associated with systemic and ocular complications. While keratopathy being the most prevalent, affecting 70–100% of long-term users, amiodarone-associated optic neuropathy (AAON), though rare (incidence: 0.36–2%), can induce diverse visual impairments, ranging from mild deficits to profound vision loss. Given that patients on amiodarone frequently possess the risk factors of vascular diseases, it is essential to differentiate the diagnosis of AAON from non-arteritic anterior ischemic optic neuropathy (AION). This study reports a 61-year-old man who developed both corneal deposition and optic neuropathy during systemic amiodarone therapy. We further analyze the clinical features of keratopathy and optic neuropathy caused by amiodarone through a comprehensive literature review, aiming to enhance diagnostic recognition and management strategies.